Myth and the Construction of Meaning in Mediated Culture - Salomé Sola Morales (KOME: An International Journal of Pure Communication Inquiry, 2013)
Traditionally mythical thought has been banished and considered lessimportant than logical thinking. However, in the last decades several authors have claimed the need to revalorize this notion. From our perspective, myth is a key concept to explore the construction of meaning in media narratives. For instance, if we try to solve fundamental questions as what communication is or how mediamake meaning, we should take into consideration the epistemological scope of myth. This article’s main objective is to prove that the co-implication between logos and mythos is essential to understand social communication and mediated culture. Thus, to avoid any kind of reductionism, it is necessary to establish a dialogue between the two forms of thinking and expression: the concept and the imagination.